2018
DOI: 10.1111/rge.12170
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of Pb–Zn Mineralization Beneath the Xiangshan Uranium Orefield, South China: Constraints from H–O–S–Pb Isotopes and Rb–Sr Dating

Abstract: The volcanic‐hosted Xiangshan uranium orefield is the largest uranium deposit in South China. Recent exploration has discovered extensive Pb–Zn mineralization beneath the uranium orebodies. Detailed geological investigation reveals that the major metallic minerals include pyrite, sphalerite, galena, and chalcopyrite, whilst the major non‐metallic minerals include quartz, sericite, and calcite. New δ18Ofluid and δDfluid data indicate that the ore‐forming fluids were mainly derived from magmatic, and the sulfide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The magmatic‐hydrothermal fluid exsolving from the silicate melt is expected to be Cl‐rich owing to the strong partitioning of Cl between the silicate melt and aqueous fluid and likely had a composition dominated by dissolved NaCl and CaCl 2 (Webster & Mandeville, 2007). Numerous previous studies of O, H, and S isotope geochemistry have demonstrated a magma‐derived ore‐forming fluids and a dominantly magmatic sulphur source for the Pb–Zn mineralization (Guo et al, 2018; Nie et al, 2018; Yang, 2015). In addition, the Pb–Zn mineralization was almost simultaneous with the crystallization of the subvolcanic rock suites (Guo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The magmatic‐hydrothermal fluid exsolving from the silicate melt is expected to be Cl‐rich owing to the strong partitioning of Cl between the silicate melt and aqueous fluid and likely had a composition dominated by dissolved NaCl and CaCl 2 (Webster & Mandeville, 2007). Numerous previous studies of O, H, and S isotope geochemistry have demonstrated a magma‐derived ore‐forming fluids and a dominantly magmatic sulphur source for the Pb–Zn mineralization (Guo et al, 2018; Nie et al, 2018; Yang, 2015). In addition, the Pb–Zn mineralization was almost simultaneous with the crystallization of the subvolcanic rock suites (Guo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies of O, H, and S isotope geochemistry have demonstrated a magma‐derived ore‐forming fluids and a dominantly magmatic sulphur source for the Pb–Zn mineralization (Guo et al, 2018; Nie et al, 2018; Yang, 2015). In addition, the Pb–Zn mineralization was almost simultaneous with the crystallization of the subvolcanic rock suites (Guo et al, 2018). Hence, we propose that the Cl‐rich fluid reflected by S‐Ap 1 and S‐Ap 2 may be derived from related magma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6a-c). At the same time, iron-rich minerals such as pyrite, chalcopyrite and biotite are commonly found in the Egongtang uranium deposit, indicating that the migration of Fe 2þ may be affected by various occurrences in the process of hydrothermal alteration (Guo, 2014;Li et al 2016).…”
Section: A3 Element Migration Rulesmentioning
confidence: 99%